2022
DOI: 10.1097/qad.0000000000003417
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osteopontin relates to myocardial fibrosis and steatosis and to immune activation among women with HIV

Abstract: Objective:Women with HIV (WWH) have heightened heart failure risk. Plasma OPN (osteopontin) is a powerful predictor of heart failure outcomes in the general population. Limited data exist on relationships between plasma OPN and surrogates of HIV-associated heart failure risk.Design:Prospective, cross-sectional.Methods:We analyzed relationships between plasma OPN and cardiac structure/function (assessed using cardiovascular magnetic resonance imaging) and immune activation (biomarkers and flow cytometry) among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…They suggest that sST-2 in PLWH may be a mediator of the myocardial fibrosis extensively described in CMR studies. A direct link between myocardial fibrosis and inflammation was offered by 2 recent studies performed in women with HIV, demonstrating, respectively, a correlation between plasma osteopontin, a predictor of heart failure, myocardial fibrosis and the expression of 2 important chemokine receptors central to myocardial inflammation, CCR2 and CX3CR1 (C-X3-C motif chemokine receptor 1) in monocytes, 123 and a correlation between myocardial fibrosis, reduced diastolic function, and elevated systemic monocyte activation. 81 While our understanding of myocardial inflammation in HIV remains incomplete, the increased circulating levels of Gal-3 and sST-2 in PLWH highlight potential pathways through which HIV may contribute to myocardial fibrosis, suggesting new avenues for targeted therapeutic interventions and research.…”
Section: Inflammatory Biomarkers and Cytokines Associated With Myocar...mentioning
confidence: 99%
“…They suggest that sST-2 in PLWH may be a mediator of the myocardial fibrosis extensively described in CMR studies. A direct link between myocardial fibrosis and inflammation was offered by 2 recent studies performed in women with HIV, demonstrating, respectively, a correlation between plasma osteopontin, a predictor of heart failure, myocardial fibrosis and the expression of 2 important chemokine receptors central to myocardial inflammation, CCR2 and CX3CR1 (C-X3-C motif chemokine receptor 1) in monocytes, 123 and a correlation between myocardial fibrosis, reduced diastolic function, and elevated systemic monocyte activation. 81 While our understanding of myocardial inflammation in HIV remains incomplete, the increased circulating levels of Gal-3 and sST-2 in PLWH highlight potential pathways through which HIV may contribute to myocardial fibrosis, suggesting new avenues for targeted therapeutic interventions and research.…”
Section: Inflammatory Biomarkers and Cytokines Associated With Myocar...mentioning
confidence: 99%
“…However, as osteopontin is involved in a variety of physiological and pathophysiological conditions [4], the specificity to a condition like heart failure -in particular in a population without CVD -may be relatively low, limiting the clinical significance of findings. This is particularly relevant in the context of studying a large set of biomarkers and the associations between them in a relatively small group of women, as was done by Robinson and team, and reported in this issue and a related publication [20,27]. As with any study performing multiple comparisons, and in particular in research involving multiple biomarkers, it is important to take into account the risk of detecting spurious associations [28].…”
mentioning
confidence: 99%
“…The study team found that plasma osteopontin was significantly associated with cardiac-MRI-derived intramyocardial triglyceride content and plasma growth differentiation factor 15 (GDF-15) -surrogate markers for myocardial steatosis and cardiac fibrosis, respectively. GDF-15 is a robust prognostic marker of and involved in myocardial pathophysiological processes underlying heart failure [19,20]. Both intramyocardial triglyceride content and GDF-15 are reported to be elevated and to be associated with preclinical markers of CVD in men and women with HIV [21][22][23].…”
mentioning
confidence: 99%
See 1 more Smart Citation